Adsorption of Glucagon and Insulin on an Immobilized Metal Ion Affinity Chromatography Silica Matrix - Cristiane S. Farinas; Sônia M.A. Bueno; Everson A. Miranda (Adsorption Science & Technology)
Glucagon is a hormone that increases blood glucose concentrations and is used as a pharmaceutical product mainly in the treatment of hypoglycaemia associated with diabetes. Given both its importance and high current cost, improved purification processes are in demand. By using immobilized metal ion affinity chromatography (IMAC), we conducted tests aimed at the purification of glucagon from complex mixtures. Adsorption studies of glucagon, insulin and a mixture of the two on adsorbents of silica–IDA–Me 2+ (Cu 2+ , Ni 2+ and Zn 2+ ) were carried out. Fixed-bed chromatographic experiments were performed and the adsorption affinity verified for all three metals tested. The most promising condition for glucagon and insulin separation was achieved by using Ni 2+ as the metal ligand and desorption with a pH step gradient. Two industrial insulin-processing fractions (one glucagon-rich and the other insulin-rich) were evaluated qualitatively under these conditions, resulting in an increase in glucagon purity for both fractions with a purification factor of five for the latter.